Industrias culturales y economía creativa en Latinoamérica - Hernández Acosta, Javier; Carolina Redondo Méndez, Andrea; Ospina Martínez, Oswaldo (Editorial Uniagustiniana, 2018)
This book aims to be a starting point to highlight the role of the academy in regards to cultural and creative industries through an effort of a group of scholars from the region who have been connected to the creative ecosystem. Essays and investigations present a sample of the research agenda needed by the sector. The book includes an overview from the role of creative and cultural industries in the economic and social development to entrepreneurs´ experiences and challenges of achieving sustainable business models. The chapters published in this work are excellent starting points for the most important conversations we will face in the coming years. The first part aims to bring the reader closer to a general context of both the description of the current situation and the opnening to opportunities offered by the formalization, support, and development of cultural activities. In the second part, it is recognized that the countries of Latin America and the Caribbean are culture producers and, therefore, have been identifying opportunities and finding, in the creative economy, a sustainable main activity of their economies.